Creativity research in medicine and nursing: A scoping review - Alex Thabane; Sarah Saleh; Sushmitha Pallapothu; Tyler McKechnie; Phillip Staibano; Jason W. Busse; Goran Calic; Ranil Sonnadara; Sameer Parpia; Mohit Bhandari (PLoS ONE, 2025)
Background Creativity fuels societal progress and innovation, particularly in the field of medicine. The scientific study of creativity in medicine is critical to understanding how creativity contributes to medical practice, processes, and outcomes. An appraisal of the current scientific literature on the topic, and its gaps, will expand our understanding of how creativity and medicine interact, and guide future research. Objectives We aimed to assess the quantity, trends, distribution, and methodological features of the peer-reviewed on creativity in medicine. Methods We searched the MEDLINE, EMBASE, and PsycINFO databases for peer-reviewed primary research publications on creativity in medicine. Screening, full-text review, and data extraction were performed independently and in duplicate by pairs of reviewers, with discrepancies resolved by a third reviewer. We performed descriptive analyses, graphically displaying the data using charts and maps where appropriate. Results Eighty-one studies were eligible for review, enrolling a total of 18,221 physicians, nurses and midwifes across all studies. Most research on creativity in medicine was published in the last decade, predominately in the field of nursing (75%). Researchers from Taiwan (22%) and the United States (21%) produced the most eligible publications, and the majority research was cross-sectional in nature (54%). There was substantial variability in the definitions of creativity adopted, and most studies failed to specify a definition of creativity. Forty-five different measurement tools were used to assess creativity, the most popular being divergent thinking tests such as the Torrance Test of Creative Thinking (24%) and Guilford Creativity Tests (16%). Conclusions Peer-reviewed scientific research on creativity in medicine, mostly conducted in the nursing profession, is sparse and performed on variable methodological grounds. Further scientific research on the topic, as well as the development of medicine-specific definitions and measurement tools, is required to uncover the utility of creativity in the medical domain.